Ring Theory - Khattar, Dinesh; Agrawal,Neha (Newdelhi : Ane Books, 2022)
This textbook has been designed for the UG/PG students of mathematics for all universities in India. It is primarily based on the classroom lectures the authors gave at the University of Delhi. This book could be used both for self-study as well as course text. Full details of all proofs are included along with innumerous solved problems interspersed throughout the text and at places where they naturally arise to understand abstract notions.
Keywords: Ring Theory